Hiv/aids education for adolescents based at sma negeri 4 pangkajene and the islands - Nurhikmah; Taher, Rusli (Journal of Evidence-Based Community Health, 2024)
Comprehensive sexual education can equip individuals with knowledge about condom use, hygiene of sexual equipment, and other risk reduction strategies. Additionally, understanding the importance of HIV testing and counseling can encourage routine testing behavior, allowing individuals to manage risks and engage in safer sexual practices. Video-based health information outreach activities related to HIV-AIDS prevention were held at SMA Negeri 4 Pangkajene and Islands, using several methods, namely the first stage method of distributing brochures to teenagers about HIV/AIDS education, the second stage, health education related to preventing HIV disease. The third stage is filling out questionnaires to teenagers regarding HIV-AIDS prevention. The results of measuring the knowledge of students at SMA Negeri 4 Pangkep showed that the average level of knowledge before the counseling was carried out was 65.00% good knowledge and 35.00% poor knowledge. Meanwhile, the average level of knowledge after counseling was found to be good knowledge of 98.00%, and poor knowledge of 2.00%. Health education media about HIV/AIDS can increase students' knowledge regarding preventing HIV/AIDS. It is important to increase knowledge about HIV-AIDS and the role of the media in the form of leaflets, videos, television, newspapers and the internet in disseminating information about HIV-AIDS to teenagers, so that stigma and discrimination against PLWHA can be minimized